Comparative Transcriptome Analysis During the Seven Developmental Stages of Channel Catfish (Ictalurus punctatus) and Tra Catfish (Pangasianodon hypophthalmus) Provides Novel Insights for Terrestrial Adaptation - Ma, Xiaoli; Shang, Mei; Su, Baofeng; Wiley, Anne; Bangs, Max; Alston, Veronica; Simora, Rhoda Mae; Nguyen, Mai Thi; Backenstose, Nathan J. C.; Moss, Anthony G.; Duong, Thuy-Yen; Wang, Xu; et al. (Frontiers in Genetics, 2021)
Tra catfish (Pangasianodon hypophthalmus), also known as striped catfish, is a facultative air-breather using swim bladder as an air-breathing organ (ABO). A related species in the same order (Siluriformes), channel catfish (Ictalurus punctatus), does not possess an ABO and thus cannot breathe in the air. Tra and channel catfish serve as great comparative models for investigating possible genetic underpinnings of aquatic to land transitions, as well as for understanding genes that are crucial for development of the swim bladder and the function of air-breathing in tra catfish. In this study, hypoxia challenge and microtomy experiments collectively revealed critical timepoints for the development of the air-breathing function and swim bladder development stages in tra catfish. Seven developmental stages in tra catfish were selected for RNA-Seq analysis based on their transition to a stage that could live at 0 ppm oxygen. More than 587 million sequencing clean reads were generated, and a total of 21, 448 unique genes were detected. A comparative genomic analysis between channel catfish and tra catfish revealed 76 genes that were present in tra catfish, but absent from channel catfish. In order to further narrow down the list of these candidate genes, gene expression analysis was performed for these tra catfish specific genes. Fourteen genes were inferred to be important for air-breathing. Of these, HRG, GRP and CX3CL1 genes were identified to be the best candidates of genes related to the air-breathing ability in tra catfish. This study provides a large data resource for functional genomic studies in air-breathing function in tra catfish, and sheds light on the adaptation of aquatic organisms to the terrestrial environment.